Investigation of thermodynamic and microstructural characteristics of NiTiCu shape memory alloys produced by arc-melting method - Tatar, Cengiz; Acar, Rauf; Qader, Ibrahim Nazem (Springer Heidelberg, 2020)
Ni50-xTi50Cux (at.%) x=14,17,20) shape memory alloys were produced using the arc-melting technique. The replacing Cu element into Ti-rich NiTi alloy has been investigated through characterization techniques, including differential scanning calorimetry (DSC), X-ray diffraction (XRD), optical and SEM microscopy. Additionally, various phases and precipitations were determined using EDS measurement. The manufactured alloys showed a single-step austenite <-> martensite phase transformation (B2 <-> B19 ). The DSC results showed that the samples have comparable high-temperature hysteresis in the range of about (30-50 K). The main detected XRD peaks are the monoclinic martensite phase with cubic austenite phases, which their intensities were decreased by increasing copper addition into the alloy. The microhardness results revealed that the second phase of the alloys has higher hardness compared to the matrix phase. It was concluded that NiTiCu can be used in low-temperature shape memory alloys as they illustrate transformation temperature below 100 degrees C
Keywords: Martensitic-Transformation; Phase-Transformation; Deformation; Temperatures; Behavior; Kinetics